2002
DOI: 10.1002/1438-9312(200208)104:8<463::aid-ejlt463>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

N-3 fatty acids and conjugated linoleic acids of longissimus muscle in beef cattle

Abstract: The objective of the experiment with cattle was to produce high quality beef under different feeding conditions and to increase the concentration of essential fatty acids in muscle. In total 10 German Simmental (GS) bulls and 9 German Holstein (GH) steers were kept either on pasture (grass feeding) or in stable (concentrate feeding). Despite biohydrogenation in the rumen, linolenic acid (C18:3n‐3) contained in grass was absorbed and deposited into the lipids of muscle. This led to a significantly (p ≤ 0.05) hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
56
5
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 31 publications
16
56
5
5
Order By: Relevance
“…The proportion of PUFA in phospholipids is controlled by the system of desaturases and elongases responsible for the conversion of essential C18:2n-6 and C18:3n-3 to long-chain PUFA . As reported by Nuernberg et al (2002) and as shown in our study, the high availability of C18:3n-3 in the diet resulted in an enhanced absorption of this FA and its conversion to C20:5n-3, C22:5n-3, and C22:6n-3. Long-chain PUFA are beneficial to human health due to their anti-atherogenic, antithrombotic, and anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of PUFA in phospholipids is controlled by the system of desaturases and elongases responsible for the conversion of essential C18:2n-6 and C18:3n-3 to long-chain PUFA . As reported by Nuernberg et al (2002) and as shown in our study, the high availability of C18:3n-3 in the diet resulted in an enhanced absorption of this FA and its conversion to C20:5n-3, C22:5n-3, and C22:6n-3. Long-chain PUFA are beneficial to human health due to their anti-atherogenic, antithrombotic, and anti-inflammatory effects.…”
Section: Discussionsupporting
confidence: 92%
“…different muscles from a group of doublemuscled bulls fed different diets (data from [68]). Similar findings are reported for pork [4,72] and sheep [55,58]. A clear inverse relationship between P/S ratio and total intramuscular fat exists for beef, as shown in Figure 2 based on a set of literature data (n = 113).…”
Section: Effect On P/s Ratiomentioning
confidence: 79%
“…However, beef from steers fed P and PG showed ratio values lower than 2.0 (Table 4), whereas beef from feedlot steers showed a mean ratio value of 2.79 (P < 0.05). Similar results have been reported by other authors (Enser et al, 1998;Nuernberg et al, 2002;Schor et al, 2008;De la Fuente et al, 2009) who have also found that the n-6:n-3 ratio increases as the grain or concentrate content in the diet increases.…”
Section: Longissimus Thoracis Intramuscular Fatty Acid Compositionmentioning
confidence: 99%